Development of antifungal biocomposite film against postharvest pathogens Colletotrichum gloeosporioides and Lasiodiplodia theobromae. (2021) - Nair, U.K. Aruna; Periyar Selvam, S.; Dharini, V.; Nambiar, Reshma B.; Anand Babu, P.; Sadiku, Emmanuel Rotimi; Jayaramudu, J.
Abstract: Colletotrichum gloeosporioides and Lasiodiplodia theobromae are the two main causative agents for the postharvest losses in mango, through anthracnose and stem-end rot disease, respectively. Reduction of these losses using antifungal agents was attempted by developing biocomposite films based on polyvinyl alcohol reinforced with cellulosic fibres incorporated with antifungal extracts. Thereafter, individual films were incorporated with aqueous (3 mg/ml) and supercritical fluid (SCF) [1000 µL] extracts of Prosopis juliflora and Acacia albida which gave the maximum inhibition in the antifungal assay of the extract against the selected pathogens. The developed films were tested for antifungal activity, tensile strength, and elongation. The films retain their antifungal activity after incorporation and also maintained significant tensile strength and elongation for a biocomposite packaging film.